2013
DOI: 10.1371/journal.pone.0064373
|View full text |Cite|
|
Sign up to set email alerts
|

High Mobility Group Box-1 Promotes the Proliferation and Migration of Hepatic Stellate Cells via TLR4-Dependent Signal Pathways of PI3K/Akt and JNK

Abstract: BackgroundThe migration of hepatic stellate cells (HSCs) is essential to the hepatic fibrotic response, and recently High-mobility group box 1 (HMGB1) has been shown up-regulated during liver fibrosis. Nevertheless, whether HMGB1 can modulate the proliferation and migration of HSCs is poorly understood, as well as the involved intracellular signaling. In this study, we examined the effect of HMGB1 on proliferation, migration, pro-fibrotic function of HSCs and investigated whether toll-like family of receptor 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(63 citation statements)
references
References 47 publications
2
61
0
Order By: Relevance
“…However, recently, the role of HMGB1 extended to include inflammation and necrosis (22). Activated monocytes and macrophages secrete HMGB1 and promote immune-stimulatory signaling (23). On the other hand, damaged cells 'passively' release HMGB1 into the extracellular environment (24), which could explain the dose-dependent response demonstrated in our data (Figs.…”
Section: Discussionmentioning
confidence: 68%
“…However, recently, the role of HMGB1 extended to include inflammation and necrosis (22). Activated monocytes and macrophages secrete HMGB1 and promote immune-stimulatory signaling (23). On the other hand, damaged cells 'passively' release HMGB1 into the extracellular environment (24), which could explain the dose-dependent response demonstrated in our data (Figs.…”
Section: Discussionmentioning
confidence: 68%
“…HMGB1 also has a synergistic effect with transforming growth factor β1 (TGF-β1) to stimulate expression of fibrogenic protein (for example, collagen α2 and α-SMA) in HSCs (72). HMGB1 promotes the proliferation/migration of HSCs and liver fibrosis partly via TLR4-MyD88 and the MAPK-NF-κB pathway ( Figure 4B) (72,73). These studies have demonstrated that HMGB1 and its profibrotic function may be effective targets to treat liver fibrosis.…”
Section: Hmgb1 and Liver Fibrosismentioning
confidence: 97%
“…In addition, knowing that HMGB1 conveys immunogenicity of the dying cell (38), the elevation of HMGB1 in lung endothelial cells challenged with ceramide may put forward the hypothesis that the ceramide-SPH-HMGB1 pathway participates in the autoimmune features of emphysema pathogenesis. Recent studies showed that HMGB1 promotes proliferation through Akt signaling pathway in hepatic stellate cells (39). Moreover, in mouse mesangial cells, HMGB1 increased the proliferation index, and the process was accompanied by down-regulation of p16…”
Section: In Lung Cancer P16mentioning
confidence: 97%